Moral Competence and Moral Orientation in Robots - Schmiljun, André (ETHICS IN PROGRESS, 2019)
Two major strategies (the top-down and bottom-up strategies) are currently discussed in robot ethics for moral integration. I will argue that both strategies are not sufficient. Instead, I agree with Bertram F. Malle and Matthias Scheutz that robots need to be equipped with moral competence if we don’t want them to be a potential risk in society, causing harm, social problems or conflicts. However, I claim that we should not define moral competence merely as a result of different “elements” or “components” we can randomly change. My suggestion is to follow Georg Lind’s dual aspect dual layer theory of moral self that provides a broader perspective and another vocabulary for the discussion in robot ethics. According to Lind, moral competence is only one aspect of moral behavior that we cannot separate from its second aspect: moral orientation. As a result, the thesis of this paper is that integrating morality into robots has to include moral orientation and moral competence.